SEEING GREEN ECONOMIC GOALS IN ACHIEVING MASHLAHAH THROUGH ISLAMIC ECONOMIC POINTS - Amrina, Dania Hellin; Kuswanto , Arif; Hakim, Dani Amran (Journal of Applied Islamic Economics and Finance, 2024)
The purpose of this study is to determine the goals of the green economy in achieving benefits through an Islamic economic perspective. The analysis states that this study uses a qualitative descriptive method using data collection techniques from secondary data, namely, studies of book libraries, journals, websites, newspapers, and magazines. The results of the study show that the concept of the green economy is compatible with Islamic economics. This is evidenced by several principles of a green economy that are in accordance with Islamic economics, including principles of Islamic social and business ethics, principles of protecting the environment and reducing social problems, principles of sustainable development, and policies that include the preservation of religion, preservation of soul, preservation of mind, preservation of mind, and maintenance of a property.